PENGEMBANGAN TEKNOLOGI BAGI PENINGKATAN PENDAPATAN PETANI TAMBAK GARAM DI DESA BULU CINDEA - Rahmi, Rahmi; Syarif, Asriyanti; Ibrahim, Juliani; Yani, Fitri Indah; Nanda, Abd. Rakhim; Mansida, Amrullah (Universitas Mataram, 2024)
Salt is one of the pond products relied upon by the community in Bulu Cindea Village. The potential for salt in this village is very abundant because raw materials are available at any time. However, the management process is still simple and untouched by technological development. This potential can be maximally developed through the development of geomembrane technology, which is proven to maximize yields and increase income for villagers. The method used by this service team is the socialization and development of salt pond demonstration plots with geomembrane technology. The development of this technology produces the best-quality salt with a relatively short harvest time, so as to increase the selling value of salt products. This community service program can be an example for other villagers, so that later it will have an effect on increasing the knowledge and welfare of residents. This community service activity positively impacted the knowledge of participating villagers, as measured by post-test scores of villagers reaching 74% after implementing this program.